The Role of Visual Identity Design and Digital Technology in Developing Local Photography Studio Entrepreneurship: A Case Study of Natsume Studio Foto Cianjur - Akbar, Aldi Mohamad; Soegoto, Eddy Soeryanto; Wahdiniwaty, Rahma; Sumitra, Irfan Dwiguna; Bachtiar, Adam Mukharil; Mohamad Akbar, Aldi (International Journal of Research and Applied Technology (INJURATECH), 2025)
The rapid growth of digital technology has reshaped entrepreneurial practices in the creative industry, including local photography studios. However, many creative MSMEs have not yet optimized visual identity design and digital media as strategic business assets. This study examines the role of visual identity design and digital media in supporting entrepreneurial development within a local photography studio. Using a qualitative case study approach, data were collected through visual observation, semi- structured interviews, and documentation of promotional media. The findings show that consistent visual identity design supported by digital platforms helps build a professional image, strengthen consumer trust, enhance brand recognition, and improve competitiveness. This study underscores the importance of visual identity and digital media as strategic and accessible tools for sustaining local creative enterprises in the digital era.